PERANCANGAN SISTEM PENAWARAN STARTUP DAN INVESTOR ONLINE - Grace Levina Dewi; Suhatati Tjandra; Setya Ardhi; Alfira Jessica (LPPM STMIK STIKOM Indonesia, 2021)
In terms of establishing and nurturing startups, finances are required to ensure their long-term viability. Startups at this stage require the support of investors as financial backers. The dearth of forums for promoting companies makes it difficult for developers to get traction and attract investors. The bidding method for entrepreneurs and investors was designed with these limits in mind. The waterfall concept is used in the design of this offering system, in which the website design is completed consecutively from beginning to end. The purpose of this website's design is to make it easier for developers to advertise startups or